Day 3 Wed, January 15, 2020 2020
DOI: 10.2523/iptc-19690-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid Stimulation-Best Practices for Design, Selection and Testing of Acid Recipes in Low Permeability Carbonate Reservoirs

Abstract: Acid stimulation in low permeability carbonates is challenging and the performance depends on a good choice of acid recipe and comprehensive testing that supports the extent of wormholes or fracture patterns. In this paper, a comprehensive testing proposal that involves initial enhancements to reaction kinetic for organic, inorganic and composite recipes and later supported by core tests to quantify optimized pore-volume to breakthrough (PVBT) times for optimum worm-hole propagation is discussed. A protocol is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Acid treatment is carried out by injecting acid solutions into the formation to dissolve rock minerals in order to expand existing and create new fractures, increase the overall permeability, and therefore the productivity of the well. Several types and combinations of acids can be used for acidizing, but the most commonly used acids are hydrochloric acid (HCl) and hydrofluoric acid (HF) [9][10][11][12]. HCl reacts with carbonate rocks such as dolomite, calcite and siderite.…”
Section: Nas Rk Is Pleased To Announce That News Of Nas Rk Series Of Geology and Technical Sciences Scientific Journal Has Been Accepted mentioning
confidence: 99%
“…Acid treatment is carried out by injecting acid solutions into the formation to dissolve rock minerals in order to expand existing and create new fractures, increase the overall permeability, and therefore the productivity of the well. Several types and combinations of acids can be used for acidizing, but the most commonly used acids are hydrochloric acid (HCl) and hydrofluoric acid (HF) [9][10][11][12]. HCl reacts with carbonate rocks such as dolomite, calcite and siderite.…”
Section: Nas Rk Is Pleased To Announce That News Of Nas Rk Series Of Geology and Technical Sciences Scientific Journal Has Been Accepted mentioning
confidence: 99%
“…The theory of an RD was first applied to study the electrochemical processes using an RDE (Daguenet 1968;Ellison et al 1971;Chin and Litt 1972;Nanis and Klein 1972;Vahdat and Newman 1973;Bruckenstein and Miller 1977;Mohr and Newman 1976;Albery and Bruckenstein 1983;Dong et al 2008), and was later adopted to analyze the chemical dissolution reactions using RDA (Boomer et al 1972;Lund et al 1973, Lund et al 1975Fredd and Fogler 1998;Taylor et al 2004;Alkhaldi et al 2010;Rabie et al 2014;Khalid et al 2015;Aldakkan et al 2018;Hall-Thompson et al 2020;Sayed et al 2020;Kotb et al 2021).…”
Section: Turbulence In the Rotating Disk Apparatusmentioning
confidence: 99%
“…First, a poor design of acid stimulation can lead to fast and uncontrolled acid/mineral dissolution, which could generate a low penetration radius and the loss of compression forces near the well. 4 Second, well integrity issues can be related to corrosion through tubing and injection equipment due to undesirable acid−metal interactions. 5 Different investigations have shown that the failure rate of acid jobs around the world is about 30%, mainly due to poor candidate selection, lack of mineralogical information, improper chemical selection (main acid, additives, strength, and volume), improper fluid placement, and shutting-in acid treatment for too long.…”
Section: Introductionmentioning
confidence: 99%